Essentials of negotiation - Lewicki, Roy J. (McGraw-Hill/Irwin, 2007)
Essentials of negotiation, 4e is a short paperback derivative from the main text, negotiation, 5e. It explores the major concepts and theories of the psychology of bargaining and negotiation, and the dynamics of interpersonal and inter-group conflict and its resolution. Fourteen of the 20 chapters from the main text have been included (about half have been shortened by about 1/3) for this volume. Chapters are shortened by removing more 'academic' material and some of the boxes. This effectively leaves the message and theories of negotiation intact.